THE IMPACT OF TEAM TEACHING ACTIVITIES ON THE STUDENTSâ READING COMPREHENSION DEVELOPMENT - N, Kurniawan Yudhi; Mazizah, Chilyatul (Language Circle: Journal of Language and Literature, 2016)
This paper presents the result of experimental research on reading comprehension development, conducted to students at state vocational high school in Central Java. Around seventy-one students participating in this research was categorized into two classes named Control and Experiment. To make it easier to understand, the result was presented in the form of statistical data. Referring to the analysis result of posttest, it shows that the Experimental class has higher learning progress than that of control class, which is 78.61 for experimental class and 66.62 for control class. Further, sig (2tailed) which is 0.00 explains that there is a significant difference between the class of Control and Experiment in term of learning achievement in the end of the program.